It Takes a Village to Raise a Child: Understanding and Expanding the Concept of the “Village” - Reupert, Andrea; Straussner, Shulamith Lala; Weimand, Bente; Maybery, Darryl (Frontiers in Public Health, 2022)
This perspective article defines and discusses the concept of the “village” when working with families who are experiencing multiple adversities. The article starts with a discussion on what is meant generally by a village approach, followed by a historical overview of how families living in adversity have been defined and positioned. The need to move past a siloed, professional centric approach when working with families is then presented. Using a model of social connections, based on Bronfenbrenner's ecological theory, we then identify who the “villagers” might be. Some potential principles for how the village might work with families living with adversity are presented, along with two case studies, to demonstrate how these principles might be enacted. This perspective article provides an overview and discussion of “the village” concept, rather than present a definitive set of guidelines or recommendations.